Interaction of surface cations of cleaved mica with water in vapor and liquid forms - Franceschi, Giada; Brandstetter, Sebastian; Balajka, Jan; Sokolović, Igor; Pavelec, Jiří; Setvín, Martin; Schmid, Michael; Diebold, Ulrike (Faraday discussions, 2024)
Natural minerals contain ions that become hydrated when they come into contact with water in vapor and liquid forms. Muscovite mica - a common phyllosilicate with perfect cleavage planes - is an ideal system to investigate the details of ion hydration. The cleaved mica surface is decorated by an array of K+ ions that can be easily exchanged with other ions or protons when immersed in an aqueous solution. Despite the vast interest in the atomic-scale hydration processes of these K+ ions, experimental data under controlled conditions have remained elusive. Here, atomically resolved non-contact atomic force microscopy (nc-AFM) is combined with X-ray photoelectron spectroscopy (XPS) to investigate the cation hydration upon dosing water vapor at 100 K in ultra-high vacuum (UHV). The cleaved surface is further exposed to ultra-clean liquid water at room temperature, which promotes ion mobility and partial ion-to-proton substitution. The results offer the first direct experimental views of the interaction of water with muscovite mica under UHV. The findings are in line with previous theoretical predictions.